Biological production of methanol by using pectin methylesterase (PME) - Ernie Zayani, Kamaruzaman (2015)
Methanol contains only one carbon atom (CH3OH) is the simplest alcohol that also known as wood alcohol. It is a colourless liquid, volatile, flammable and poisonous in properties. It is widely used in several industries such as plastic industry. It also been used as an original feedstock to make polymer. This research study was focus on the production of methanol by using pectin methylesterase (PME). This research study consists of two objectives. The first objective of this research was to produce methanol by using pectin methylesterase (PME). The second objective was to analyse the factors that affecting the methanol production from pectin methylesterase (PME). The raw material, lime peels waste and the substrate, pectin solution were prepared. The extractions of PME from lime peels were done. PME and pectin were mixed for enzymatic reaction process. The experiment for the preliminary study was performed. Preliminary study was performed with five factors which were pH, temperature, concentration of NaCl, agitation and enzymatic reaction time to know the highest production of methanol. Design experiment by using Design Expert software was done after preliminary experiment finished. The analysis to know the production of methanol was performed by using high performance liquid chromatography (HPLC). The result of preliminary experiment by using HPLC showed that the highest concentration produced was at pH 7 and temperature of 70 °C with 5 hours enzymatic reaction time and 3 M of concentration of NaCl. The results of 18 runs sample from Design Expert software were analysed by using Response Surface Methodology (RSM) through Fractional Factorial Design (FFD). The results showed that the range yield of methanol was between 0.3 – 2.2g/g. The main effect analysis showed that concentration of NaCl had contributed the most in methanol production with percentage contribution of 45.36%. The result of interaction between factors showed that the interaction between factor A (pH) and factor B (temperature) at pH 5 and 70 °C produced the highest methanol with 13.22 % contribution. The value of R2 for the regression analysis was 0.9904. Hence, the methanol was successfully produced from pectin methylesterase (PME) by using lime peels waste.